Optimizing nitrogen rate and planting density for sunflower under irrigated conditions of Punjab - Rasool, K; Wajid, A; Sanaullah, -; Ghaffar, A; Shoaib, M; Arshad, M; Abbas, S (SAARC Journal of Agriculture, 2015)
A field study was conducted at different nitrogen rates on growth, yield and achene oil content of sunflower sown at different planting densities at Faisalabad, Punjab, Pakistan. Randomized complete block design with split plot arrangement was applied, having plants densities (8.33, 6.67 and 5.56 plants m-2) in main plots and while various nitrogen levels (90, 120 and 150 kg ha-1) in sub-plots. The plant densities and various nitrogen levels had a significant effect on leaf area index, crop growth rate, 1000-achene weight, head diameter, number of achenes head- 1,biological yield, oil quality, harvest index and achene yield of sunflower. The plants which were fertilized at 150 kg N ha-1 gaveabout 24% more achene yield as compared to 90 kg N ha-1. More oil content was obtained in plots where nitrogen was applied at the rate of 90 kg ha-1. It can be concluded that nitrogen application at the rate of 150 kg ha-1 with planting density (8.33 plants m-2) produced highest achene yield. SAARC J. Agri., 13(1): 174-187 (2015)